Glycinebetaine Biosynthesis in Response to Osmotic Stress Depends on Jasmonate Signaling in Watermelon Suspension Cells - Xu, Zijian; Sun, Mengli; Jiang, Xuefei; Sun, Huapeng; Dang, Xuanmin; Cong, Hanqing; Qiao, Fei (Frontiers in Plant Science, 2018)
Glycinebetaine is an important non-toxic osmo-protectant, which is accumulated in higher plants under various stresses. The biosynthesis of glycinebetaine acchieved via is a two-step oxidation from choline and betaine aldehyde, catalyzed by choline monooxygenase (CMO) and betaine aldehyde dehydrogenase (BADH), respectively. Up-regulated gene expression of BADH and CMO induced by stress is clearly observed, but the signal transduction is poorly understood. Here, glycinebetaine accumulation in response to osmotic stress and growth recovery induced by exogenous glycinebetaine were observed in a watermelon cell line. When tracing back to the genome sequence of watermelon, it shows that there exists only one member of ClCMO or ClBADH corresponding to glycinebetaine biosynthesis. Both genes harbor a CGTCA-motif in their promoter region which is involved in methyl jasmonate (MeJA)-responsiveness. Amongst MeJA, Ethephon, abscisic acid (ABA) and salicylic acid (SA), MeJA was most effective in gene inducing the expression of ClCMO and ClBADH, and the accumulation of glycinebetaine could also reach an amount comparable to that after osmotic stress by mannitol. Moreover, when ibuprofen (IBU), a JA biosynthesis inhibitor, was pre-perfused into the cells before osmotic stress, glycinebetaine accumulation was suppressed significantly. Interestingly, newly grown cells can keep a high content of glycinebetaine when they are sub-cultured from osmotic stressed cells. This study suggests that osmotic stress induced glycinebetaine biosynthesis occurs via JA signal transduction and not only plays a key role in osmotic stress resistance but also contributes to osmotic stress hardening.